2012
DOI: 10.1111/j.1745-4549.2012.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF Γ-Irradiation ON THE PHYSICOCHEMICAL PROPERTIES, AND MICROBIAL AND SENSORY QUALITIES OF COLD-STORED ONION PUREE

Abstract: The present study was conducted to evaluate the effect of different doses (0, 1, 2, 3, 5 and 7 kGy) of γ‐irradiation on the physicochemical properties (pH, titratable acidity, total soluble solid, color, organic acid content), and also the microbial and sensory qualities of onion puree during cold storage at 4C for 28 days. The different doses of γ‐irradiation were found to not have any negative effect on titratable acidity, pH, total soluble solid and organic acid contents of onion puree immediately after irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
(67 reference statements)
0
11
2
Order By: Relevance
“…Similarly, Miller and McDonald (1999) have demonstrated that there was no alteration in pH of papaya juice that had undergone irradiation treatment. In contrast, Sadoughi, Karim, Hashim, Zainuri, and Ghazali (2012) observed there was no significant difference (P 40.05) in the pH of onion puree at different irradiation doses (1-7 kGy) from the initial value of pH 4.55, nor was there any significant change during the 28-day storage period.…”
Section: Resultscontrasting
confidence: 75%
See 3 more Smart Citations
“…Similarly, Miller and McDonald (1999) have demonstrated that there was no alteration in pH of papaya juice that had undergone irradiation treatment. In contrast, Sadoughi, Karim, Hashim, Zainuri, and Ghazali (2012) observed there was no significant difference (P 40.05) in the pH of onion puree at different irradiation doses (1-7 kGy) from the initial value of pH 4.55, nor was there any significant change during the 28-day storage period.…”
Section: Resultscontrasting
confidence: 75%
“…Fan et al (2005) reported irradiation doses at 0.5 and 1.0 kGy did not change the TA values of sliced apples, which were initially treated with 7% calcium ascorbate. In contrast, Sadoughi et al (2012) observed that there was no significant difference (P 40.05) in the TA of onion puree at different irradiation doses (1-7 kGy). The identification and quantitative analysis of major organic acids in fruits is considered very important for quality evaluation of food and beverages (Hasib, Jaouad, Mahrouz, & Khouili, 2002).…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…γ‐Irradiation of onion puree at 2 kGy has been found to have a number of advantages (Sadoughi et al . ). The most important effect of this process is a reduction in bacteria and yeast counts making it safe for at least 1 month at 4C.…”
Section: Introductionmentioning
confidence: 97%